QUALITY EVALUATION OF WINES FROM KOSOVO AND METOHIJA: POLYPHENOLS CONTENT, ANTIOXIDANT ACTIVITY AND ELEMENTAL COMPOSITION - Jevtić, Sonja; Mutić, Jelena; Djurdjić, Sladjana; Babincev, Ljiljana; Gurešić, Dejan; Stanković, Dalibor M.; Petković, Branka B. (Bulletin of Natural Sciences Research, 2022)
Wine is a very rich source of polyphenols and essential elements which have multiple biological activities. This study evaluates the total phenolic content (TPC), antioxidant activity (AA) of sixteen wine samples made from different grape varieties in the territory of Kosovo and Metohija, mostly from the area of Orahovac and Velika Hoča. The obtained results, determined by using the Folin-Ciocalteu assay, showed that wines from territory of Kosovo and Metohija are rich in polyphenols, with TPC ranges from 276±16 to 371±46 (white wines) and  1467±32 to 2823±43 mg gallic acid equivalents GAE/L (red wines). The total antioxidant activities, determined by ABTS method, range from 8.7±0.4 to 22.8±0.7 mmol trolox equivalents TE/L for red wines and from 1.3±0.1 to 3.8±0.3 mmol TE/L for white wines. Elemental content of studied wines showed certain difference between wines from nearby regions.
Keywords: Polyphenols; Antioxidant activity; Wine; Elemental composition